2017
DOI: 10.1155/2017/9205062
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Carvedilol in the Cardiac Immune Response Induced by Experimental Infection with Trypanosoma cruzi

Abstract: Trypanosoma cruzi causes a cardiac infection characterized by an inflammatory imbalance that could become the inciting factor of the illness. To this end, we evaluated the role of carvedilol, a beta-blocker with potential immunomodulatory properties, on the immune response in C57BL/6 mice infected with VL-10 strain of T. cruzi in the acute phase. Animals (n = 40) were grouped: (i) not infected, (ii) infected, (iii) infected + carvedilol, and (iv) not infected + carvedilol. We analyzed parameters related to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“… 7 , 12 In particular, our group has recently observed that Cv therapy in mice infected with the VL-10 strain of T. cruzi was capable to reduce the plasma levels of the CCL2 chemokine and to elevate the levels of IL-10 reflecting in the reduction of the inflammatory process in the cardiac tissue. 13 However, opposing our expectancies, the current results using the inflammatory strain of the T. cruzi (Colombian strain) implied that Cv therapy worsened T. cruzi infection course in the murine model, enhancing mortality rate, parasitaemia, and leukocyte infiltration as well as increasing the circulating levels of inflammatory chemokines.…”
Section: Discussioncontrasting
confidence: 73%
“… 7 , 12 In particular, our group has recently observed that Cv therapy in mice infected with the VL-10 strain of T. cruzi was capable to reduce the plasma levels of the CCL2 chemokine and to elevate the levels of IL-10 reflecting in the reduction of the inflammatory process in the cardiac tissue. 13 However, opposing our expectancies, the current results using the inflammatory strain of the T. cruzi (Colombian strain) implied that Cv therapy worsened T. cruzi infection course in the murine model, enhancing mortality rate, parasitaemia, and leukocyte infiltration as well as increasing the circulating levels of inflammatory chemokines.…”
Section: Discussioncontrasting
confidence: 73%
“…Our group has investigated the use of different medicines in clinical practice (simvastatin, doxycycline, angiotensin-enzyme converter inhibitor, beta-blocker, and others) alone or in association with benznidazole to reduce the release of cytokines IFN-g, TNF, IL-6, IL-10 and chemokines (CCL2, CCL3, CCL4, CCL5, CXCL9, CXCL11, CCL1, CCL17, CCL20, CCL24, and CCL26) and minimize inflammatory infiltration into the heart, which is important to ameliorate the consequences of T. cruzi antigens. However, these events trigger fibrosis formation and cardiac morphological and functional damage (Silva et al, 2012;de Paula Costa et al, 2016;Horta et al, 2017;Leite et al, 2017). These cytokines can shift the regulation patterns described during the acute and chronic courses of T. cruzi infection, affecting the parasite-host equilibrium and driving the pathogenesis process (Talvani and Teixeira, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Carvedilol has also been shown to decrease the production of ROS, such as H 2 O 2 , which is responsible for driving calcium overload in HF [ 24 ]. In a study on experimental infection with Trypanosoma cruzi , carvedilol decreased CCL2 levels and increased the levels of the anti-inflammatory cytokine IL-10, resulting in decreased inflammatory infiltration in cardiac muscle [ 25 ].…”
Section: β-Blockersmentioning
confidence: 99%